A simple device to rapidly prepare whole mounts of murine intestine. - Rudling, R; Hassan, A; Kitau, J; Mandir, N; Goodlad, R (2006)
Many mouse models of neoplasia and pre-neoplasia require the examination of whole mounts of the gastrointestinal tract. A simple device has been produced to facilitate the rapid preparation of mouse intestines for subsequent quantification of tumours and pre-neoplastic lesions such as aberrant crypt foci. The device greatly speeds up the production of whole mounts and also provides far more consistent and better-quality preparations.